Reforming European Data Protection Law - Gutwirth, Serge; Leenes, Ronald; de Hert, Paul.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book on privacy and data protection offers readers conceptual analysis as well as thoughtful discussion of issues, practices, and solutions. It features results of the seventh annual International Conference on Computers, Privacy, and Data Protection, CPDP 2014, held in Brussels January 2014. The book first examines profiling, a persistent core issue of data protection and privacy. It covers the emergence of profiling technologies, on-line behavioral tracking, and the impact of profiling on fundamental rights and values. Next, the book looks at preventing privacy risks and harms through impact assessments. It contains discussions on the tools and methodologies for impact assessments as well as case studies. The book then goes on to cover the purported trade-off between privacy and security, ways to support privacy and data protection, and the controversial right to be forgotten, which offers individuals a means to oppose the often persistent digital memory of the web. Written during the process of the fundamental revision of the current EU data protection law by the Data Protection Package proposed by the European Commission, this interdisciplinary book presents both daring and prospective approaches. It will serve as an insightful resource for readers with an interest in privacy and data protection.
Keywords: Law; Philosophy; Computer security; Computers and civilization; Computers; Law and legislation; Human rights; International law; Intellectual property -- Law and legislation; Law; International IT and Media Law, Intellectual Property Law; Legal Aspects of Computing; Philosophy of Technology; Human Rights; Systems and Data Security; Computers and Society; Electronic books